Stimulatory effects of NESFATIN‐1 on meiotic and developmental competence of porcine oocytes. Issue 10 (25th February 2019) - Cao, Zubing; Luo, Lei; Yang, Jie; Zhang, Ling; Gao, Di; Xu, Tengteng; Tong, Xu; Zhang, Dandan; Wang, Yiqing; Li, Yunsheng; Fang, Fugui; Zhang, Yunhai
Abstract: NESFATIN‐1 acts as a neuroendocrine hormone to suppress gonadotropin secretion in the female goldfish and to prevent germinal vesicle breakdown of oocytes in the zebrafish. However, the expression and function of NESFATIN‐1 in meiotic maturation and development of porcine oocytes remains elusive. Genomic structure of porcine NESFATIN‐1 precursor nucleobindin 2 ( NUCB2 ) is first characterized in detail and an evolutionally closer relationship of NESFATIN‐1 between pig and rat is shown by phylogenetic analysis of multiple species. Additionally, immunofluorescence analysis revealed that NESFATIN‐1 is predominantly expressed and localizes on the membrane of both theca cells and granulosa cells, but not expressed in oocytes. Real‐time quantitative polymerase chain reaction showed that the abundance of NESFATIN‐1 transcripts in granulosa cells progressively decreases during the developmental transition from small follicles to large follicles. Correspondingly, NESFATIN‐1 could significantly enhance both the cleavage and blastocyst rate of parthenogenetically activated oocytes from small follicles ( p < 0.05), whereas it did not affect meiotic maturation and development of oocytes from large follicles. Interestingly, we found that NESFATIN‐1 significantly improves meiotic maturation of oocytes cultured in chemically defined medium in the absence of pyruvate compared with the control group ( p < 0.05), suggesting that the NESFATIN‐1 as a substitute for pyruvate exerts beneficial effects on porcine oocyte maturation. In conclusion, these results demonstrate that NESFATIN‐1 facilitates both meiotic maturation and development of porcine oocytes. Abstract : NESFATIN‐1 facilitates both meiotic maturation and development of porcine oocytes.